Analisis Tindak Tutur Langsung dan Tidak Langsung Percakapan Shabira Alula dan Ayahnya di Sosial Media Tiktok - Sri Deviayu Ningsi; Abdul Munir; Nurcholish Nurcholish (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This study aims to describe the Forms of Direct and Indirect Speech Acts of Conversations by Shabira Alula and Her Father on Tiktok Social Media. The type of research used is descriptive qualitative research. Data collection techniques use observation techniques by watching video conversations and listening. The researcher started collecting data since Shabira was 3 years old, from 30 June 2021 to 30 June 2022. The results of this study are that there are 107 data in the form of direct speech and 5 data in indirect speech. Direct speech is divided into three types, namely interrogative, imperative, and declarative. There are 107 interrogative utterances (question words). imperative utterances (command sentences) amount to 24 data. declarative speech (sentence news) amounted to 16 data. Imperative speech is divided into several parts, namely the utterance of asking is 6 sentences, while the indirect speech act contains 2 fragments of conversation.